A 3D gradient-enhanced micropolar damage-plasticity approach for modeling quasi-brittle failure of cohesive-frictional materials. (15th October 2020) - Neuner, M.; Gamnitzer, P.; Hofstetter, G.
Highlights: A micropolar gradient-enhanced framework for cohesive-frictional materials. Mesh-objective representation of non-associated plasticity and material failure. The GMCDP model, a micropolar gradient-enhanced constitutive model for concrete. Application of the proposed framework to 3D large scale finite element simulations. Validation of the GMCDP model based on experimental results. Abstract: Continuum models based on the combination of the theories of plasticity and damage mechanics pose a powerful framework for representing the highly nonlinear material behavior of cohesive-frictional materials. However, non-associated plastic flow rules for representing the inelastic volumetric expansion of such materials may result in unstable material behavior and, accordingly, strongly mesh-dependent results in finite element simulations. Regularization techniques such as the gradient-enhanced continuum or similar nonlocal approaches, which work well for regularizing mode I failure, are often not sufficient as a remedy. In contrast to the latter, the theory of the micropolar continuum represents a suitable framework for regularizing non-associated plastic flow and shear band dominated failure properly, but it fails to do so for mode I failure. Hence, in the present contribution, a combination of the theories of the micropolar continuum and the gradient-enhanced continuum for regularizing both shear band dominated failure and mode I failure is presented. By incorporating a 3D damage-plasticity model for concrete into the proposed framework, it is demonstrated that the proposed model constitutes a physically sound and numerically stable approach for modeling the nonlinear material behavior of concrete in both the pre-peak and the post-peak regime for a broad variety of loading conditions.